2012
DOI: 10.1111/mec.12062
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite length variation in candidate genes correlates with habitat in the gilthead sea bream Sparus aurata

Abstract: The genetic basis and evolutionary implications of local adaptation in high gene flow marine organisms are still poorly understood. In several Mediterranean fish species, alternative migration patterns exist between individuals entering coastal lagoons that offer favourable conditions for growth and those staying in the sea where environmental conditions are less subject to rapid and stressful change. Whether these coexisting strategies are phenotypically plastic or include a role for local adaptation through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 73 publications
3
24
2
1
Order By: Relevance
“…A particular focus was made on microsatellite markers located close to 2 candidate genes, GH and Prl, that are functionally related to growth and osmoregulatory capacities in fish (Streelman & Kocher 2002, Almuly et al 2008, Quéré et al 2010) and have been previously showed to be involved in habitat-based genetic differentiation in sea bream (Chaoui et al 2012). This latter study suggested that GH and Prl genotypes with varying selective advantage among lagoons impact mortality in juvenile sea breams that spent their first year of life in ecologically contrasted lagoons (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A particular focus was made on microsatellite markers located close to 2 candidate genes, GH and Prl, that are functionally related to growth and osmoregulatory capacities in fish (Streelman & Kocher 2002, Almuly et al 2008, Quéré et al 2010) and have been previously showed to be involved in habitat-based genetic differentiation in sea bream (Chaoui et al 2012). This latter study suggested that GH and Prl genotypes with varying selective advantage among lagoons impact mortality in juvenile sea breams that spent their first year of life in ecologically contrasted lagoons (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesised that under habitat-based selection, genetic differentiation would be higher in older juveniles caught in autumn than in younger ones caught soon after entering coastal lagoons. Therefore, we randomly selected 12 autumn individuals from MA and 12 autumn individuals from TH to evaluate genetic differentiation between the 2 most extreme habitats (Chaoui et al 2012). New primers were designed to amplify the full gene sequences of GH and Prl genes using long-range PCR (LR-PCR) (see LR-PCR pri mers in Table S1 in Supplement 1).…”
Section: Next-generation Sequencing Of Gh and Prl Long-range Ampliconsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, lagoon individuals were found to be genetically differentiated from individuals inhabiting the buffered open sea environment (Allegrucci et al 1997, Lemaire et al 2000. Further studies of other marine, coastal, euryhaline fish species by, e.g., Blel et al (2010;Mugil cephalus), Chaoui et al (2012;Sparus aurata), González-Wangüemert and Pérez-Ruzafa (2012; Diplodus sargus) and González-Wangüemert and Vergara-Chen (2014; Pomatoschistus minutus) reported similar (but still not fully understood) observations. However, the absence of recognized polymorphic markers in GHR, and the non-significant relationship between gene expression level of IGF-1 and genotypes at the μIGF-1 locus in UFW, SSW and SFW individuals does not allow us to go any further with regard to a possible genotype-phenotype relationship in sea bass.…”
Section: Discussionmentioning
confidence: 94%